2013
DOI: 10.1021/jm400658e
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase IV and Its Inhibitors: Therapeutics for Type 2 Diabetes and What Else?

Abstract: The proline-specific dipeptidyl aminopeptidase IV (DPP IV, DPP-4, CD26), widely expressed in mammalians, releases X-Pro/Ala dipeptides from the N-terminus of peptides. DPP IV is responsible of the degradation of the incretin peptide hormones regulating blood glucose levels. Several families of DPP IV inhibitors have been synthesized and evaluated. Their positive effects on the degradation of the incretins and the control of blood glucose levels have been demonstrated in biological models and in clinical trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(143 citation statements)
references
References 131 publications
(200 reference statements)
4
130
0
1
Order By: Relevance
“…These incretins, which have been shown to have an insulinotropic activity during the post-prandial phase, contribute to the regulation of serum glucose levels in humans. Therefore, inhibition of DPP-IV is a strategy which is being employed, notably with pharmaceutical drugs (gliptins) to help in 15 the management of type 2 diabetes 99 . Several food protein hydrolysates have been shown to display DPP-IV inhibitory properties in vitro 100 .…”
Section: Peptidesmentioning
confidence: 99%
“…These incretins, which have been shown to have an insulinotropic activity during the post-prandial phase, contribute to the regulation of serum glucose levels in humans. Therefore, inhibition of DPP-IV is a strategy which is being employed, notably with pharmaceutical drugs (gliptins) to help in 15 the management of type 2 diabetes 99 . Several food protein hydrolysates have been shown to display DPP-IV inhibitory properties in vitro 100 .…”
Section: Peptidesmentioning
confidence: 99%
“…ORTEP diagram of the A and B molecules. particular has been reported to be important for safety 11,30 . Rummey et al reported the homology models of DPP8 and DPP9 based on the DPP-4 X-ray structure, and suggested that the selectivity of sitagliptin was based on the absence of key interactions in DPP8/9 31 .…”
Section: Co-crystal Structure Of Dpp-4 With Anagliptinmentioning
confidence: 99%
“…Until recently, various inhibitors of DPP-4 were developed by chemical design and synthesis, as well as by biological evaluation with consideration for hypoglycaemic activity and -as a safety concern -with consideration for selectivity against DPP-4-related proteases such as DPP8, DPP9 and fibroblast activation protein (FAP). These efforts resulted in numerous inhibitors; the eight inhibitors shown in Figure 1 are currently available for use 11 . Sitagliptin was the first of these inhibitors to be approved, gaining authorization in 2006 in the US and in 2007 in the EU.…”
Section: Introductionmentioning
confidence: 99%
“…This is a new molecular target correlated with type 2 diabetes development. This ubiquitous enzyme has been shown to cleave and inactivate glucagon-like peptide-1 (GLP-1) and glucose dependent insulinotropic polypeptide (GIP) in the postprandial phase, leading to a loss in their insulinotropic activity (Juillerat-Jeanneret, 2014). In order to exert this activity, a peptide should have a hydrophobic character, a length varying from 2 to 8 amino acid residues, and contain a Pro residue located at the first, second, third, or fourth N-terminal position (Lammi, Zanoni, Arnoldi, & Vistoli, 2016).…”
Section: Bioactivities Of Peptides From In Silico Digestion Of Pruninsmentioning
confidence: 99%